Taking the single route- the good, the bad and the expectations. - Tan, Cherlyn Jin Ping. (2013)
Given the rising trend of women delaying (or eschewing) marriage and the dearth of studies on their subjective experiences of singleness, this research aims to critically examine how singlehood is commonly understood and to find new ways of thinking and talking about singleness. Drawing on in-depth interview data, I find that while there may be noteworthy variations in the ways that women belonging to different age groups experience singlehood, such one-sided representation of singleness fails to capture the multiple aspects of a woman’s single identity and the plurality of meanings that she attaches to marriage and singlehood. To complete the discussion on contemporary singleness, the paper concludes with an analysis of how single women make sense of their own lives living in a society where marriage continues to be the norm.